PROCEDURAL ASPECTS REGARDING SMUGGLING'S CRIME - TUDOR (BARBU), Corina-Maria (International Journal of Legal and Social Order, 2022)
For romanian's judicial authorities, smuggling's crime investigation is and will be put to the test by the ingenious ways of evading the customs obligations applied by the people who commit such an illegal act and who often prove difficult to detect. Although the smuggling's crime prosecution and trial is not carried out in the framework of a special procedure, I appreciated that it is necessary to analyze, through the lens of cases from judicial practice, the ways of notifying the investigators regarding the commission of such an act, the methods and the techniques used for the collected evidence administration proveding crime's commission, the preventive measures taken, the civil action initiated, as well as the trial phase, whether the criminal investigation was completed with the notification of the court through the indictment, or by concluding a plea agreement.